Slownik angielsko polski : 1351 ilustrowanych slowek dla dzieci i mlodziezy - Bortolussi, Lee Ann.; Donghi, Guiseppe; Koziorowska, Krystyna (Warszawa : WILGA, 1995)
An illustrated English/Polish dictionary of 1351 words for children and teenagers. Ages 7-15.
Keywords: Picture dictionaries, Polish -- Juvenile literature; Picture dictionaries, English -- Juvenile literature; Picture dictionaries; English language -- Dictionaries -- Polish